A Sweet Vaccination – the Deadly Hershey’s Kiss - Ann H. Williams (American Society for Microbiology, 2011)
In Immunology courses, concepts such as primary and secondary immune response and the topic of vaccinations can be difficult to visualize for students. Described here is a short activity where students choose and snack on candy to simulate primary and secondary immune responses in the context of a vaccination. This short interactive activity is performed in the lecture course of Immunology, an upper-division Biology course that contains mostly Biology major juniors or seniors (class of 30–40). It is performed on the first day of class, and is consistently referred to as the semester progresses and more complex and detailed topics are introduced. It is utilized to help students understand and visualize the process of primary immune response, secondary immune response, immunological memory, and vaccinations.